Analysis on the Influence of Place Branding Strategies on Rural Tourism : A Unified Theory of Acceptance and Use of Technology (UTAUT) Approach—A Case Study of Kampung Agong (International Journal of Creative Future and Heritage (TENIAT), 2025)
Abstract This study delves into the intricate dynamics of rural tourism development through the lens of the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, applied to the context of place branding strategies. Focused on Kampung Agong as a case study, the research aims to comprehensively evaluate the impact of place branding initiatives, encompassing performance expectation, effort expectation, social influence, and technological factors, on the advancement of tourism in rural locales. Using a quantitative methodology that includes structured questionnaires distributed to 128 stakeholders involved local tourism operators, government representatives, and tourists. The rationale for this selection of participants was to capture a comprehensive view of the factors influencing place branding effectiveness across different stakeholder perspectives. The study reveals the nuanced interplay between these branding strategies and the growth of tourism in Kampung Agong. By unraveling the key determinants of tourists' acceptance and utilization of technological advancements facilitated by Place Branding initiatives, insights into enhancing the sustainable growth of tourism in rural areas are unearthed. Moreover, the study contributes to understanding the dynamics of destination branding and offers insights for policymakers and practitioners seeking to enhance tourism development through strategic branding initiatives, thus fostering the socio-economic upliftment of rural communities like Kampung Agong. AbstrakKajian ini menyelidiki dinamika rumit pembangunan pelancongan luar bandar melalui lensa kerangka Teori Penerimaan dan Penggunaan Teknologi Bersepadu (UTAUT), yang digunakan dalam konteks strategi Penjenamaan Tempat. Tertumpu kepada Kampung Agong sebagai kajian kes, penyelidikan ini bertujuan menilai secara menyeluruh impak inisiatif Penjenamaan Tempat, merangkumi Jangkaan Prestasi, Jangkaan Usaha, Pengaruh Sosial dan Faktor Teknologi, terhadap kemajuan pelancongan di kawasan luar bandar. Kajian ini menggunakan metodologi kuantitatif yang merangkumi soal selidik berstruktur yang diedarkan kepada 128 pihak berkepentingan, termasuk pengendali pelancongan tempatan, wakil kerajaan, dan para pelancong. Pemilihan para responden spesifik ini adalah untuk mendapatkan pandangan yang menyeluruh mengenai faktor-faktor yang mempengaruhi keberkesanan penjenamaan tempat dari pelbagai perspektif. Kajian itu mendedahkan interaksi bernuansa antara strategi penjenamaan ini dan pertumbuhan pelancongan di Kampung Agong. Dengan merungkai penentu utama penerimaan pelancong dan penggunaan kemajuan teknologi yang difasilitasi oleh inisiatif Penjenamaan Tempat, pandangan untuk meningkatkan pertumbuhan mampan pelancongan di kawasan luar bandar digali. Selain itu, kajian itu menyumbang kepada pemahaman dinamik penjenamaan destinasi dan menawarkan pandangan untuk penggubal dasar dan pengamal yang ingin meningkatkan Pembangunan pelancongan melalui inisiatif penjenamaan strategik, sekali gus memupuk peningkatan sosio-ekonomi masyarakat luar bandar seperti Kampung Agong.
Keywords: Place branding; Rural tourism; Unified Theory of Acceptance and Use of Technology (UTAUT)